A Comprehensive Overview on Stress Neurobiology: Basic Concepts and Clinical Implications - Godoy, Lívea Dornela; Rossignoli, Matheus Teixeira; Delfino-Pereira, Polianna; Garcia-Cairasco, Norberto; de Lima Umeoka, Eduardo Henrique (Frontiers in Behavioral Neuroscience, 2018)
Stress is recognized as an important issue in basic and clinical neuroscience research, based upon the founding historical studies by Walter Canon and Hans Selye in the past century, when the concept of stress emerged in a biological and adaptive perspective. A lot of research after that period has expanded the knowledge in the stress field. Since then, it was discovered that the response to stressful stimuli is elaborated and triggered by the, now known, stress system, which integrates a wide diversity of brain structures that, collectively, are able to detect events and interpret them as real or potential threats. However, different types of stressors engage different brain networks, requiring a fine-tuned functional neuroanatomical processing. This integration of information from the stressor itself may result in a rapid activation of the Sympathetic-Adreno-Medullar (SAM) axis and the Hypothalamus-Pituitary-Adrenal (HPA) axis, the two major components involved in the stress response. The complexity of the stress response is not restricted to neuroanatomy or to SAM and HPA axes mediators, but also diverge according to timing and duration of stressor exposure, as well as its short- and/or long-term consequences. The identification of neuronal circuits of stress, as well as their interaction with mediator molecules over time is critical, not only for understanding the physiological stress responses, but also to understand their implications on mental health.